2005
DOI: 10.1136/hrt.2003.029959
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the prevalence and aetiology of left ventricular systolic dysfunction in the community: the Harrow heart failure watch

Abstract: Objective: To assess ethnic differences in the prevalence and aetiology of left ventricular systolic dysfunction (LVSD) in the community. Design: Community cohort study. All patients underwent echocardiography and those found to have LVSD underwent myocardial perfusion imaging with or without coronary angiography to diagnose underlying coronary artery disease (CAD). Setting: Seven representative general practices in Harrow, UK, a community hospital, and a local district general hospital. Patients: 1392 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…Even comparing results using the standardised rates found in other White British men (379.5) (predominantly English)—436.5 in Indian men, 592.0 in Pakistani men (table 1)—however, does not show the kind of variations seen in Leicestershire11 and Birmingham 7. Crucially, the cross sectional study by Galasko et al in Harrow, England, showed no substantial difference between South Asian and White populations 4. The 2011 results of the prevalence study in Birmingham also help interpret the conflicting findings 5.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Even comparing results using the standardised rates found in other White British men (379.5) (predominantly English)—436.5 in Indian men, 592.0 in Pakistani men (table 1)—however, does not show the kind of variations seen in Leicestershire11 and Birmingham 7. Crucially, the cross sectional study by Galasko et al in Harrow, England, showed no substantial difference between South Asian and White populations 4. The 2011 results of the prevalence study in Birmingham also help interpret the conflicting findings 5.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, it is not possible to identify the specific cause of heart failure from the data we have since ICD code I50 does not distinguish valvular, rheumatic, ischaemic or other causes. In the UK setting, valvular and rheumatic heart disease are uncommon causes of heart failure 4 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 A UK study of left ventricular systolic dysfunction, found that non-Europids, the majority of whom were SA, had similar rates of left ventricular systolic dysfunction as Europids. 48 In contrast, in a retrospective cohort study from the UK of 5789 patients newly admitted with HF (336 SA, mean age 70, 43% women; 5057 Europid, mean age …”
Section: Heart Failure I) Prevalencementioning
confidence: 91%
“…Indians have a higher hospital admission rate for congestive heart failure compared with the Chinese population in Singapore 12 . In Britain, Galasko and colleagues 13 showed that South Asians had a higher prevalence of coronary artery disease (CAD) as the underlying cause of left ventricular systolic dysfunction than do white patients 13 . Included in the limited published data on the management of heart failure in India is the very important consideration of patient compliance following the prescription of appropriate treatment 14 .…”
Section: Epidemiology Of Cardiovascular Diseasementioning
confidence: 99%